Small bowel obstruction through an internal hernia caused by a congenital mesenteric defect: an early diagnosis and prompt treatment of a rare condition saved a young life - Chimarios, Maria; Wong, Candance; Alapati, Amulya; Bhatia, Shubham; Louis, Martine; Shah, Darshak (International Surgery Journal, 2025)
Congenital internal hernias causing small bowel obstruction are extremely rare in adults, with only approximately 28 cases reported in the literature. The condition carries a high mortality rate-up to 50% even with treatment, and nearly 100% without intervention. Diagnosis is particularly challenging due to the nonspecific nature of symptoms and often inconclusive imaging findings. We present a patient diagnosed with a trans mesenteric hernia resulting from a congenital defect. The patient failed conservative management, which included bowel rest, nasogastric tube placement, and monitoring with KUB X-rays. A diagnostic laparoscopy was performed and subsequently converted to a laparotomy. Intraoperative findings revealed a 6 cm defect in the mesentery with approximately 60 cm of small bowel herniating through, showing signs of early ischemia. Bowel viability was restored following reduction, and the mesenteric defect was closed. Congenital mesenteric defects, though rare, are an important consideration in the differential diagnosis of de novo small bowel obstruction, particularly in adults with a virgin abdomen and no history of prior abdominal surgery. Early recognition and prompt surgical intervention are essential, as timely management can significantly reduce the risk of morbidity and mortality.